The Impact Of CRM Implementation On Customer Satisfaction, Loyalty And Organisational Profitability - Tanas, Islam Nazier Abdelmalak (2010)
This research investigates to what extend the customer relationship management implementation affects the customer loyalty and maintaining profitability in the food and retail industry by cultivating intrinsically motivated loyalty between customers and retailers in the current competitive environment. The former grocery retailers caught up in traditional transaction-based strategies and relied on acquisition instead of loyalty which deters customers from choosing alternative retailers by increasing the cost associated with switching. In contrast, other retailers foster loyalty through relationship marketing to increase the customer’s value of the relationship. The main objective of this research is to examine a link between the implementation of customer relationship management and increasing the level of customers’ store satisfaction, loyalty, and increased retailer profitability with the rewards provided by the Clubcard. The results of the research showed that more satisfied customers with the provided rewards are the most loyal customers to the retailer, i.e. Clubcard holders allocated a higher proportion of their budget and frequently patronage to the retailer more than customers are not holding Clubcard.